MIGRATIONS, IDENTITY POLITICS, AND CITIZENSHIP QUESTION IN ASSAM: RESOLVING THE PUZZLE - Kavita Sharma * , Rohit Kumar ** (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
The debate and tensions which have been gained ground around the question of citizenship and non-citizenship, since the adoption of National Register of Citizens and Citizenship Amendment Act by the Bharatiya Janata Party, not only attained the centrality of Indian political discourse but highlighted some deep-rooted historical problems of our society. Assam witnessed the worst of the consequences and became the hotbed of the protests when these have been executed there without deeply reflecting upon the issues of the problem. This article depicts that how migrations caused the problem of socio-cultural mix and resulted into social polarization which led to the tensions of resource use and distribution between the native people of the state and the migrants in Assam. This socio-cultural-identity complex gave birth to the politics of cultural identity-based polarizations and politics in Assam. Identity based politics further deepen the conflict and shaped it in permanent identities of insiders and outsiders. The article offers an extensive historical explanation of the events and politics around the attempts made to resolve the question of legal and illegal citizens of the state which failed due to the half-heartedness of the attempts at similar and nature of the problem. The article concludes by presenting that how the Assam’s present problem of citizenship and non-citizenship is rooted in the history of migrations and identity politics which now shaped into ideological polarization keeping in mind the electoral/political benefits of the regime after 2014.